Molecular cloning and characterization of common marmoset SULT1C subfamily members that catalyze the sulfation of thyroid hormones. Issue 10 (9th August 2021) - Kurogi, Katsuhisa; Manabe, Yoko; Liu, Ming-Cheh; Suiko, Masahito; Sakakibara, Yoichi
ABSTRACT: Cytosolic sulfotransferase SULT1C subfamily is one of the most flexible gene subfamilies during mammalian evolution. The physiological functions of SULT1C enzymes still remain to be fully understood. In this study, common marmoset ( Callithrix jacchus ), a promising primate animal model, was used to investigate the functional relevance of the SULT1C subfamily. Gene database search revealed 3 intact SULT1C genes and a pseudogene in its genome. These 4 genes were named SULT1C1, SULT1C2, SULT1C3P, and SULT1C5, according to the sequence homology and gene location. Since SULT1C5 is the orthologous gene for human SULT1C2P, we propose, here, to revisit the designation of human SULT1C2P to S ULT1C5P . Purified recombinant SULT1C enzymes showed sulfating activities toward a variety of xenobiotic compounds and thyroid hormones. Kinetic analysis revealed high catalytic activities of SULT1C1 and SULT1C5 for 3, 3′-T2 . It appears therefore that SULT1C isoforms may play a role in the thyroid hormone metabolism in common marmoset. Graphical Abstract: